2023
DOI: 10.3390/biom13091412
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Blueberry Extracellular Vesicles and Their Gene Regulation Effects in Intestinal Caco-2 Cells

Yangfan Leng,
Liubin Yang,
Hangxin Zhu
et al.

Abstract: Plant extracellular vesicles (P-EVs) are considered promising functional food ingredients due to their various health benefits. In this study, blueberry extracellular vesicles (B-EVs) were collected and purified by size exclusion chromatography (SEC). The chemical compounds in B-EV extracts were analyzed by LC-MS/MS. In addition, the stability of B-EVs was evaluated during short- and long-term storage, heating, and in vitro digestion. The results showed that the B-EVs had a desirable particle size (88.2 ± 7.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Existing preservation of PDNVs is mainly done by simply lowering the temperature, with most of the PDNVs being stored at −80 °C, some of the PDNVs undergo liquid nitrogen flash freezing and then stored at −80 °C, and there are also studies of storing them at −20 °C or place them at 4 °C for short-term preservation. There have been some studies evaluating the storage of PDNVs at different temperatures for short periods of time, and they found that 1 month's storage at some temperatures caused these PDNVs to undergo morphological changes, mainly in the form of aggregation or fusion [ 112 ]. Of course, this is related to the origin of the plant, some PDNVs are relatively more stable, and different PDNVs may be suitable for storage at different temperatures [ 112 ].…”
Section: Key Considerations: the Challenge Of Stability And Reproduci...mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing preservation of PDNVs is mainly done by simply lowering the temperature, with most of the PDNVs being stored at −80 °C, some of the PDNVs undergo liquid nitrogen flash freezing and then stored at −80 °C, and there are also studies of storing them at −20 °C or place them at 4 °C for short-term preservation. There have been some studies evaluating the storage of PDNVs at different temperatures for short periods of time, and they found that 1 month's storage at some temperatures caused these PDNVs to undergo morphological changes, mainly in the form of aggregation or fusion [ 112 ]. Of course, this is related to the origin of the plant, some PDNVs are relatively more stable, and different PDNVs may be suitable for storage at different temperatures [ 112 ].…”
Section: Key Considerations: the Challenge Of Stability And Reproduci...mentioning
confidence: 99%
“…There have been some studies evaluating the storage of PDNVs at different temperatures for short periods of time, and they found that 1 month's storage at some temperatures caused these PDNVs to undergo morphological changes, mainly in the form of aggregation or fusion [ 112 ]. Of course, this is related to the origin of the plant, some PDNVs are relatively more stable, and different PDNVs may be suitable for storage at different temperatures [ 112 ]. Some studies have shown that the effect of transdermal treatment of melanoma with aloe vera-derived nanovesicles as a delivery vehicle for indocyanine green (ICG) remains after storage for some time [ 113 ].…”
Section: Key Considerations: the Challenge Of Stability And Reproduci...mentioning
confidence: 99%